PENEGAKAN HUKUM TERHADAP PENINGKATAN KASUS PROSTITUSI ONLINE DI WILAYAH HUKUM POLDA BALI - Hesron, Paulus Erastus; Susrama, I Nengah (Jurnal Hukum Mahasiswa, 2024)
Prostitution or online prostitution is the practice of prostitution which uses the internet network or social media as a means of liaison or means of communication for pimps, sex workers and their users. This research aims to find out and explore how online prostitution cases are increasing in the jurisdiction of the Bali Regional Police. This paper uses empirical research methods using a sociological juridical approach. The results of this research show that perpetrators of online prostitution can be punished under Article 296 and Article 506 of the Criminal Code, The efforts made by the Bali Regional Police in the process of taking action against perpetrators of prostitution are preventive efforts, namely by providing education about the dangers of online prostitution and repressive efforts in the form of arresting pimps to receive punishment in accordance with existing laws and regulations.